Assessment of knowledge and practice of nurses regarding infection prevention and associated factors at Debre Tabor Comprehensive Specialized Hospital, Northwest Ethiopia - Tafere, Tesfahun Zemene; Belachew, Tadele Biresaw; Feleke, Dejen Getaneh; Adal, Gashaw Mekete (Frontiers in Public Health, 2024)
Background: Healthcare-Acquired Infections have a major negative impact on the global healthcare delivery system, resulting in increased morbidity and mortality and excessive healthcare resource utilization. Infection prevention and control is the main healthcare agenda nation-wide. However, it remains a challenge to achieve the sustainable development goals of the healthcare issues. This study aimed to assess the nurses' knowledge and practice towards infection prevention and associated factors at Debre Tabor Comprehensive Specialized Hospital, northwest Ethiopia.: An institutional-based cross-sectional study was carried out from May 1/2021 to June 30/2021 at Debre Tabor Comprehensive Specialized Hospital, Ethiopia. A total of 219 nurses participated in this study. A stratified random sampling technique with a pre-tested structured self-administered questionnaire was used to collect data. A Multivariable logistic regression model was fitted to identify factors associated with the knowledge and practice of nurses towards infection prevention. Result: The current study showed that the overall knowledge and practice of nurses towards infection prevention was 59.4 %( 95%CI: 53.0-65.8) and 53 %( 95%CI: 46.6-59.4) respectively. Educational level of diploma [AOR: 0.8, 95%CI: 0.67-0.83], years of work experience < 10 [AOR: 1.7, 95%CI: 1.3-9.28] and being trained on infection prevention [AOR: 2.5 (2.3-8.0)] were factors that affect knowledge of nurses towards infection prevention. Moreover, < 10 years of work experience [AOR=1.5, 95%CI: 1.2-10.1] and being trained on infection prevention [AOR=2.2, 95%CI: 1.94-13.5] were factors that affect the practice of nurses towards infection prevention.Conclusions and recommendations: Most nurses were knowledgeable and had good practices.However, a substantial proportion of nurses had inadequate knowledge and practice in infection prevention. The nurses' knowledge and practice was associated with years of work experience and training status on infection prevention. Moreover, the education level of nurses was other predictor variable of knowledge of nurses.Therefore, health care workers in the hospital should adhere to the national infection prevention protocols. The policy designers should provide training for nurses on infection prevention to improve knowledge and practice towards infection prevention. Furthermore, future researchers better to conduct a qualitative study to get more detailed information.